Identification of EMT-related alternative splicing event of TMC7 to promote invasion and migration of pancreatic cancer - Weng, Yuanchi; Qian, Hao; Hong, Liwen; Zhao, Shulin; Deng, Xiaxing; Shen, Baiyong (Frontiers in Immunology, 2023)
Objective: Epithelial-mesenchymal transition (EMT) is tightly associated with the invasion and metastasis of pancreatic cancer with rapid progression and poor prognosis. Especially, gene alternative splicing (AS) event plays critical role in regulating the progression of pancreatic cancer. Therefore, this study aims to identify the EMT-related AS event in pancreatic cancer. Methods: The EMT-related gene sets, transcriptomes, and matched clinical data were respectively obtained from the MSigDB, TCGA, ICGC, and GEO databases. Key gene AS events associated with liver metastasis were identified by prognostic, GSVA, and correlation analysis in pancreatic cancer. The cell line and organoid model were constructed to evaluate these key gene AS event in XXX in vitro. Furthermore, we established an EMT-related gene set consisting of 13 genes by prognostic analysis, the role of which was validated in two other databases. Finally, human pancreatic cancer tissue and organoid model were used to evaluate the correlation between the enrichment of this gene set and liver metastasis. Results: Prognostic analysis and correlation analysis revealed that eight AS events were closely associated with the prognosis of pancreatic cancer. Furthermore, the expression of TMC7 and CHECK1 AS events were increased in the metastatic lesions of human tissue and organoid model. Additionally, the knockdown of exon17 of TMC7 significantly inhibited the proliferation, invasion, and migration of pancreatic cancer cells in 2D and 3D cell experiments. Finally, the expression of exon17 of TMC17 exhibited a significant correlation with the poor prognosis in pancreatic ductal adenocarcinoma (PDAC). Conclusion: The AS events of TMC7 and CHECK1 were associated with liver metastasis in pancreatic cancer. Moreover, the exon 17 of TMC7 could be potential therapeutic targets in pancreatic cancer.